Treating Brain Metastases from Breast Cancer: Outcomes after Stereotactic Radiosurgery. Issue 6 (June 2020) - Wilson, T.G.; Robinson, T.; MacFarlane, C.; Spencer, T.; Herbert, C.; Wade, L.; Reed, H.; Braybrooke, J.P.
Abstract: Aims: Stereotactic radiosurgery (SRS) is an alternative to surgery or whole brain radiotherapy for the control of single or multiple brain metastases in patients with breast cancer. To date, there is no clear consensus on factors that might predict overall survival following SRS. The aim of this study was to assess the overall survival of breast cancer patients with brain metastases treated with SRS at a single centre and to examine the factors that might influence survival. Materials and methods: A retrospective analysis of consecutive patients with breast cancer and brain metastases, considered suitable for SRS by the regional neuro-oncology multidisciplinary team. All patients were treated at a single National Health Service centre. Results: In total, 91 patients received SRS between 2013 and 2017, of whom 15 (16.5%) were alive at the time of analysis. The median overall survival post-SRS was 15.7 months (interquartile range 7.7–23.8 months) with no significant effect of age on survival (67 patients ≤ 65 years, 16.3 months; 26 patients > 65 years, 11.4 months, P = 0.129). The primary tumour receptor status was an important determinant of outcome: 31 oestrogen receptor positive (ER+)/human epidermal growth factor receptor 2 negative (HER2–) patients had a median overall survival of 13.8 months, 14 ER+/HER2+ patients had a median overall survival of 21.4 months, 30 ER–/HER2+ patients had a median overall survival of 20.4 months and 16 patients with triple negative breast cancer (TNBC) had a median overall survival of 8.5 months. A larger total volume of tumour treated (>10 cm 3 ), but not the number of individual metastases treated, was associated with worse survival ( P = 0.0002) in this series. Patients with stable extracranial disease at the time of SRS had improved overall survival compared with those with progressive extracranial disease (30 patients stable extracranial disease overall survival = 20.1 months versus 33 patients progressive extracranial disease overall survival = 11.4 months; P = 0.0011). Seventeen patients had no extracranial disease at the time of SRS, with a median overall survival of 13.1 months. Conclusions: This single-centre series of consecutive patients with brain metastases from breast cancer, treated with SRS, had a similar overall survival compared with previous studies of SRS. TNBC and ER+/HER2– histology, metastatic volumes >10 cm 3 and progressive extracranial disease at the time of SRS were associated with worse survival. Highlights: There is improving overall survival in breast cancer patients with brain metastases treated with stereotactic radiosurgery. Factors influencing survival post-stereotactic radiosurgery are receptor status, systemic disease control and volume of metastases treated. Patients with disease limited to the CNS had worse survival than those with stable extracranial disease, suggesting a possible role for systemic therapy in this patient subset.